The Role of High Sensitivity C-reactive Protein to Predict Delirium Persistence in Elderly Patients with Pneumonia: A Prospective Cohort Study - Roza Mulyana; Yuliarni Syafrita; Hirowati Ali; Arina Widya Murni (Interna Publishing, 2022)
Background: Delirium is a disorder of acute full attention, and cognitive function commonly occurs at elderly which  can prolong hospitalization, dependence rate, morbidity, and mortality, with pneumonia infection as one of its risk factors. Several markers have been studied for delirium, but relationship between delirium severity and persistence remains unclear. This study aimed to examine the role of hs-CRP, pNF-H, S100B, and NLR to predict delirium persistence.  Methods: A prospective  cohort study was  conducted among 80 subjects who were admitted to the internal ward in dr. M. Djamil Hospital in Padang. Subjects were grouped based on severity of delirium using the Memorial Delirium Assessment Scale and  followed up until discharged to determine delirium persistence event. Results: Mean age of subjects is 70.7±7.4 years, 39 (48.8%) male and 41 (51.2%) female,consisting of 29 mild, 26 moderate, and 25 severe delirium. Levels of hs-CRP in mild, moderate, and severe delirium are 13.36±0.79, 13.56±0.78, and 13.88±0.59 mg/L (p=0.038), respectively. Median NLR values for mild, moderate, severe delirium were 6.80 (1.00-31.00), 9.50 (3.60-46.00), and 11.90 (2.80-46.50) (p=0.026). Cut off value hs-CRP 13.61 mg/L has significant difference for delirium persistence event (OR 2,54; 95% CI 1,01-6,39). Median levels of pNF-H and S100B are not significant in different delirium severity, regardless of non-persistent or persistent. Conclusion:  Hs-CRP levels exceeding 13.61 can predict risk of persistent delirium, but not with levels pNF-H, S100B, and NLR.